Revitalisasi Perpustakaan Sekolah dalam Mengoptimalkan Literasi Informasi Siswa SD Negeri 040517 Tigajumpa - Alisa, Nur; Sayekti, Retno (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2023)
A library plays a crucial role in adding school value. Well designed library based on careful consideration will undoubtedly support its quality. However, not all school libraries adhere to the standards set out as mentioned in Article 23, paragraph (1) about library, which states that a school library space should provide for visitors comfortableness. Those condition are similarly happen in State Elementaris School 040517 Tigajumpa. The avalilable library does not meet the good standard library criteria. Therefore, the library revitalization is needed to solve this condition. This research employed is action research method, consisting of four stages: problem diagnosis, action planning, action implementation, and evaluation. Those stages were run for 1 month.